2022
DOI: 10.3390/nu14153103
|View full text |Cite
|
Sign up to set email alerts
|

The Chilean Diet: Is It Sustainable?

Abstract: Food systems are one of the main contributors to climate change. Sustainable diets are one strategy to mitigate climate change. Assessments and estimations at a national level are lacking, especially in the Global South, probably due to a lack of national surveys of food consumption and a limited interest in sustainable diets information. The objective of this study is to estimate and describe the carbon and water footprint of the Chilean population’s diet in an overall estimation desegregated by region, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…They found that mean consumption of nuts, legumes, vegetables, whole cereals, and vegetable oils was lower than recommended, and consumption of tubers & potatoes, dairy products, red meat, and added sugars was higher than recommended by the EAT-Lancet Commission. Similarly, Gormaz et al [7] reported that a representative sample of the Chilean population (≥ 2 years, n = 4920 of which 5% were children aged 2-5-year-old [31]) had low consumption of nuts, legumes, whole cereals, and vegetable oils, and high consumption of dairy products, red meat, and added sugars. Our findings also align with the results observed among European adolescents from the HELENA cohort study [32,33] showing low adherence to the planetary health diet as measured by the PHDI (mean total score = 44.3 (95% CI 43.7, 44.9) points).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that mean consumption of nuts, legumes, vegetables, whole cereals, and vegetable oils was lower than recommended, and consumption of tubers & potatoes, dairy products, red meat, and added sugars was higher than recommended by the EAT-Lancet Commission. Similarly, Gormaz et al [7] reported that a representative sample of the Chilean population (≥ 2 years, n = 4920 of which 5% were children aged 2-5-year-old [31]) had low consumption of nuts, legumes, whole cereals, and vegetable oils, and high consumption of dairy products, red meat, and added sugars. Our findings also align with the results observed among European adolescents from the HELENA cohort study [32,33] showing low adherence to the planetary health diet as measured by the PHDI (mean total score = 44.3 (95% CI 43.7, 44.9) points).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of diets in Latin America show poor alignment with the EAT-Lancet diet [7][8][9][10]; however, only a few included children in the analysis [7,8]. There is only one study internationally that has provided a detailed description of children's adherence to sustainable healthy diets [11].…”
Section: Introductionmentioning
confidence: 99%
“…EnF estimates in different regions point to differences according to the dietary standards of the territories. In South America, a study performed in Argentina showed values of 8910 g CO 2 eq/day for greenhouse gas (GHG) emissions, 54.2 m 2 /day for soil use, and 205 L/day for freshwater [ 21 ], while a study performed in Chile showed GHG and soil use values of 4670 g CO 2 eq/person/day and 4177 L/person/day, respectively [ 22 ]. In Asia, a study performed in Lebanon determined the water use of food consumption to be 2571 L/day and the GHG emissions to be 4060 g CO 2 eq/day [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Debido a la falta de encuestas nacionales sobre el consumo de alimentos no existe mucha evidencia en la región sobre el impacto de las dietas en el ambiente. En Chile, un reciente estudio [11] estimó la huella de carbono e hídrica de la dieta de la población chilena basada en la Encuesta Nacional de Consumo Alimentario realizada en 2010. Se obtuvo una huella de carbono de 4,67 kilogramos equivalentes de dióxido de carbono y una huella hídrica de 4177 litros, ambas por persona al día.…”
unclassified